3-Hydroxy-3-Phenyl-1-o-Chlorophenyltriazene: A New Reagent for Spectrophotometric Determination of Lead - Kumar Yadav, Vinod; Chauhan A.K. Goswami, R.S.; Purohit, D.N. (Asian Journal of Chemistry, 2012)
Lead(II) forms a greenish yellow complex with the reagent 3-hydroxy-3-phenly-1-o-chlorophenyltriazene at 20-40 ºC. The complex is stable and does not change thereafter. The composition of the complex (Pb : R) is 1 : 1 with absorption maximum at 394 nm and optimum pH 7.0-7.5. The molar absorptyvity and Sandell’s sensitivity values are 7750 L/mole cm and 26.73 ng/cm2 respectively at the working wavwlength 406 nm. The Beer’s law is obeyed in the concentration range 0.2 × 10-4 M - 12 × 10–4 of lead. The standard deviation (10 measurements) for 8.28 ppm of lead was found as 0.002 ppm (0.60%). The interference studies with 22 diverse cations and anions have also been performed.